830 A Case of Colo-Colonic Intussusception Secondary to A Large Lipoma in An Adult. (12th October 2021) - Koronfel, M; Jamal, A; Edmonds, R
Abstract: Colonic lipomas are benign tumours, most commonly in the right colon or caecum, usually detected incidentally at colonoscopy and are often asymptomatic not requiring treatment. Lipomas leading to intussusception have previously been described in case reports, but it remains a rare occurrence, no specific incidence data has been documented. We present the case of a patient with a 7cm colonic lipoma that developed an intussusception. This patient suffered non-specific pulling pain along the right and upper abdomen for many years. A distal ascending colonic lipoma was identified, on repeated imaging and colonoscopy and biopsied. It was concluded that the abdominal pain was due to gallstones, diverticulitis and adhesions from previous pelvic surgery. In early December 2020, the patient was reviewed and listed for elective cholecystectomy. Later the same month, the patient was admitted with severe abdominal pain, watery and bloody diarrhoea. CT scan showed the colonic lipoma had acted as the lead point for an intussusception, with the lipoma and surrounding colon having intussuscepted into the transverse colon. Patient had an open right hemicolectomy and anastomosis for colo-colic intussusception secondary to the lipoma. Subsequently, the patient developed anastomotic breakdown requiring relook laparotomy with resection of ileo-colic anastomosis and end ileostomy formation. Adults presenting with intussusception is rare and associated with nonspecific signs and symptoms. Variability in clinical presentation highlights the need for a low index of suspicion in people with known colonic masses. In addition, early surgical intervention should be considered in masses >4cm as previously suggested in the literature.